2020
DOI: 10.1080/26395916.2020.1821095
|View full text |Cite
|
Sign up to set email alerts
|

The voices of youth in envisioning positive futures for nature and people

Abstract: The unpredictable Anthropocene poses the challenge of imagining a radically different, equitable and sustainable world. Looking 100 years ahead is not easy, and especially as millennials, it appears quite bleak. This paper is the outcome of a visioning exercise carried out in a 2-day workshop, attended by 33 young early career professionals under the auspices of IPBES. The process used Nature Futures Framework in an adapted visioning method from the Seeds of Good Anthropocene project. Four groups envisioned mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 52 publications
0
24
0
1
Order By: Relevance
“…For example, we found that respondents who voted for promotion of green technologies rarely prioritized increasing nature appreciation or reducing fertility rates. The disparity in attitudes towards technology has not been brought up in recent studies on conservationists' values (e.g., Holmes et al, 2017; Sandbrook et al, 2010; Sandbrook et al, 2019) but was found to be important for sustainability science ECRs (Rana et al, 2020). As compared to technological solutions, actions strengthening nature appreciation may seem feeble for ECRs trained in natural but not in social sciences (Bennett et al, 2017; Moon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, we found that respondents who voted for promotion of green technologies rarely prioritized increasing nature appreciation or reducing fertility rates. The disparity in attitudes towards technology has not been brought up in recent studies on conservationists' values (e.g., Holmes et al, 2017; Sandbrook et al, 2010; Sandbrook et al, 2019) but was found to be important for sustainability science ECRs (Rana et al, 2020). As compared to technological solutions, actions strengthening nature appreciation may seem feeble for ECRs trained in natural but not in social sciences (Bennett et al, 2017; Moon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is thus not surprising that conservation researchers, as practitioners working towards long‐term protection of biodiversity, are extremely concerned about the global ecological crisis and the lack of progress in effectuating its counteractions (Adams, 2020; Soulé, 1985). For early‐career conservation researchers (hereafter, ECRs), it is further troubling that their voices are often not involved in building the solutions for a more sustainable future (Rana et al, 2020). Public conservation discussions need accounts from marginalized groups (Milner‐Guilland, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another effective pathway towards enhancing transformative change is the one presented by Rana et al (2020) -envisioning the futures of nature and people. This article is based on the results of a participatory scenario workshop with early career professionals at an IPBES event in Brazil that helped to identify leverage points towards sustainable and desirable futures.…”
Section: Pathways For Transformative Changementioning
confidence: 99%
“…The exercise was built on the Seeds of Good Anthropocene concept, using the Nature Futures Framework, where inspiring initiatives are characterized by having a transformative positive impact at other initiatives, sectors, existing values and more (Bennett et al 2016). In this regard, Rana et al (2020) present four envisioned and desirable futures elaborated during the workshop where humanity has organized itself, the economy, politics and technology, to achieve improved naturehuman well-being.…”
Section: Pathways For Transformative Changementioning
confidence: 99%